Changing the oxygen reaction mechanism in composite electrodes by the addition of ionic- or ambipolar-conducting phases: Series or parallel pathways. (20th June 2022) - Araújo, Allan J.M.; Loureiro, Francisco J.A.; Grilo, João P.F.; Macedo, Daniel A.; Paskocimas, Carlos A.; Fagg, Duncan P.
Highlights: CGO- and CPO-based composite electrodes for solid oxide cells. Improved catalytic behaviour of ceria with multivalent cations under high p O2 . Series pathways for ORR in C349/CGO electrodes. Parallel pathways for ORR in C349/CPO electrodes. Abstract: In this work, we conduct a systematic investigation of composite oxygen electrodes for Solid Oxide Cells (SOCs) based on the recently emerging misfit calcium cobaltite material, "Ca3 Co4 O9+ δ " – C349. Its electrochemical performance is shown to be limited by its low intrinsic level of ionic conductivity, thus, requiring the addition of an ionic-conducting composite phase. In this respect, Ce0.8 Gd0.2 O2- δ (CGO) is the state-of-the-art choice due to its excellent ionic conductivity. Nonetheless, little attention has been given to the use of alternative ionic phases, such as Ce0.8 Pr0.2 O2- δ, which also offer minor levels of p-type conductivity. Therefore, we try to elucidate the influence of this minor electronic component in this phase, on the resultant oxygen reaction mechanism of the composite electrode. We demonstrate that a preferential series pathway for the oxygen reaction occurs in the CGO-based electrode, performing better at high temperatures and low oxygen partial pressures. Conversely, the CPO-based electrode presents superior performance under highly oxidising conditions and at low temperatures, related to an increasing importance of possible parallel reaction pathways. The results are supported by a detailed mechanistic study, based on a Distribution Function of Relaxation Times (DFRT) analysis, allowing clarification of potential mechanistic models for both electrodes.